The effect of violent and non-violent computer games on cognitive performance. - Barlett, Christopher P.; Vowels, Christopher L.; Shanteau, James; Crow, Janis; Miller, Tiffany (Computers in Human Behavior, 2009)
Two studies were conducted in order to determine the impact computer games had on the cognitive performance. Study 1 evaluated a measure of cognition, which incorporates aspects of short-term working memory, visual attention, mathematical decision making, and auditory perception. Study 2 measured the cognitive performance between those who did not play video games versus those who played either a violent or non-violent video game. Results from Study 1 indicate participants needed approximately four trials to reach asymptotic performance on the cognitive measure. Results of Study 2 showed that participants who did not play any video game did not have a change in their cognitive performance, while those who played either a violent or non-violent video game had an increase in their cognitive performance. Copyright (c) 2008 Elsevier Ltd.